A Call for Better, Not Faster, Research Ethics Committee Reviews in the Covid‐19 Era. Issue 5 (8th September 2021) - Tamariz, Leonardo; Hendler, Fred J.; Wells, John M.; Anderson, Annette; Bartlett, Stephen
Abstract: With the rapid spread of SARS‐CoV2 has come a rapid proliferation of clinical research studies, resulting in considerable strain on research ethics committees (RECS), which need to review study proposals. RECs are pressured to move through the review process quickly so that studies can get underway to address the pandemic. These committees are also asked to increase efficiency without relaxing the standards for ethical review. RECs are accustomed to external pressure for approval from investigators; however, in the Covid‐19 era, this pressure is coming from not only the sponsors and investigators but also many other stakeholders, including world leaders, the community, the media, and professional organizations. Drawing on the authors' experiences on a central REC reviewing complex multicenter Covid‐19 studies, this commentary describes challenges that are inherent to Covid‐19 research studies, such as the difficulty of obtaining informed consent from patients ill with the highly infectious virus. The commentary recommends several steps that RECs can take to ensure ethical review of research studies during the Covid‐19 pandemic and future infectious disease outbreaks.